2016
DOI: 10.4314/jab.v105i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extracts effects of seeds of <i>Thevetia peruviana</i> and <i>Azadirachta indica</i> on the development of<i> Phytophthora megakarya</i> in locality of Biakoa (Cameroon)

Abstract: Objective: The objective of this work was to evaluate, the impact of aqueous extracts of seeds of "yellow oleander" Thevetia peruviana (AETP), Azadirachta indica (AEAI) "neem" and Ridomil Gold Plus 66WP in black pod disease in Cameroon during two consecutive years. Methodology and results: A completely randomize bloc device containing four treatments (control, AETP, AEAI and Ridomil R and three replications was used in the farm. Extracts were applied twice in a month at the dose of 16.67 g/l while Ridomil R wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Similarly, [34] have demonstrated the efficacy of neem extract on diseases in cherry production. [22] showed that aqueous neem seed extract inhibited growth of Phytophthora megakarya in vitro. Mancozeb 80 WP had inhibited, almost totally, the growth of P. heterocornis isolates in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, [34] have demonstrated the efficacy of neem extract on diseases in cherry production. [22] showed that aqueous neem seed extract inhibited growth of Phytophthora megakarya in vitro. Mancozeb 80 WP had inhibited, almost totally, the growth of P. heterocornis isolates in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Neem extract is known for its insecticidal [21], [22] and fungicidal [19], [22] properties. These two characteristics could open up a new avenue in the protection of crops that are generally subject to a pest complex.…”
Section: Introductionmentioning
confidence: 99%
“…Three replicates were performed for each concentration and for each isolate. The percentage of inhibition (PI) relative to the control is calculated according to the following formula of Mboussi et al (2016).…”
Section: Amendments Of Pepper Extracts To Culture Media and Transplanmentioning
confidence: 99%
“…Research reports indicate diseases due to fungi or bacteria or have been reported in Cameroon on maize, affecting its quantity and quality (William Norbert et al, 2018;Mboussi et al, 2016;Ngoh dooh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lengthening rainy season (from 3 to 4 months) in recent years in the Far North zone is a favorable condition for the development of this disease (Burns and Shurtleff, 1973). Aqueous neem extracts effectively against several pathogens that attack crops (Pohe and Agneroh, 2013;Mboussi et al, 2016;Goel et al, 2016). Therefore, this work aims to evaluate the efficiency and reduction induction of neem extract and Mancozeb 80 WP to manage Physoderma Brown Spot (PSB) and Physoderma Stalk Rot (PSR) of corn to Physoderma maydis in Far North Cameroon in field condition.…”
Section: Introductionmentioning
confidence: 99%